A rhetorical stylistic analysis of selected proverbs from the book of proverbs - Dunya A. Aljazrawi,; Zeena A. Aljazrawi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The present study aims at analyzing proverbs from the Book of Proverbs rhetorically and stylistically to identify the features of such proverbs that belong to the genre of wisdom literature which affects people’s lives significantly. The data which consists of 60 proverbs that represent the three themes under investigation were analyzed using Mann and Thompson’s (1988) model of rhetorical analysis and Simpson’s (2004) model of stylistic analysis. Data analysis yielded that the macro level (nucleus) was used more frequently than the micro level (satellite) both in the whole data and across the themes. Declarative clauses were used more frequently than imperative and interrogative ones in both cases to produce more persuasive proverbs. Compound sentences were the highest in frequency followed by complex and then simple sentences to strongly influence the readers. Using parallelism and repetition in proverbs contributed to producing more persuasive proverbs whereas adjectives and adverbs affected the way the audience felt. This study sheds light on proverbs which contribute to spreading wisdom among the readers and help them to face the challenges of life more wisely, make wise choices and differentiate between what is good and what’s bad. It also identifies the features which make those proverbs more persuasive and more coherent to help when composing new ones.